The Discovery of a Male Malay Crestless Fireback Lophura erythrophthalma (Raffles, 1822) (Aves: Galliformes: Phasianidae) at Ulu Sat Forest Reserve, Machang, Kelantan, Peninsular Malaysia - Ainun Hidayah Wahad; Wan Hafizin Idzni Wan Mohammad Hizam; Muhammad Hamirul Shah Ab Razak; Aainaa Amir; Hazizi Husain; Mohd Saupi Abdullah; Ehwan Ngadi; Mohamad Arif Iskandar Abdul Wahab; Asrulsani Jambari (Wildlife Information Liaison Development Society, 2026)
Indexed by Scopus/ERA